Empowering the Creativity of Women Traditional Culinary MSMEs in Ngawi, East Java: Innovation Strategies and Strengthening Local Economic Competitiveness - Sri Wahyuni (Brilliant International Journal Of Management And Tourism, 2026)
Micro, Small, and Medium Enterprises (MSMEs) led by women are an important pillar of the local economy in the traditional culinary sector, which is rich in cultural values. In Ngawi Regency, East Java, women MSMEs face complex challenges in innovating and increasing dynamic competitiveness and penetration of modern products. This study aims to analyze the strategies for empowering the creativity of women MSMEs in traditional culinary businesses in Ngawi, as well as the impact of product innovation capacity and strengthening local economic competitiveness, using qualitative methods with a case study approach. The findings reveal that empowering creativity occurs through: (1) adapting traditional recipes based on modern market preferences without losing the essence of the original taste (Maulid, A. & Ciptandi, F., 2023); (2) innovative packaging and attractive presentation using local materials and branding based on local wisdom narratives (Duchek, 2020); (3) utilizing digital technology for marketing and expanding distribution networks (Miya Dewi, Moh, & Burhan., 2025). Technical training support and access to capital increase their confidence and experimental abilities (Brush et al., 2019). This strategy also creates uniqueness as a key selling point, thereby strengthening their economic position within the local value chain. Empowering the creativity of women entrepreneurs in traditional culinary MSMEs in Ngawi is a key strategy for encouraging contextual, incremental innovation. The synergy of traditional knowledge, individual creativity, and external support can transform local potential into a sustainable competitive advantage (Bula, 2022).